Community Based Rice Seed Production system: Experiences from Climate Smart Village (CSV), Phailom, Lao PDR - Okumu, Benard O. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
This manual provides a snapshot of community based quality rice seed production activities drawing from experiences Climate-Smart Village (CSV), Phailom in Laos PDR. Each module in this manual consists of the following components: learning objectives, methodology, content, and resources.